ANALISIS PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN IPS SD - Ika Sholihatul Maulida; Dewi Widiana Rahayu; Muhammad Thamrin Hidayat; Suharmono Kasiyun (Universitas Negeri Medan, 2020)
The purpose of this research was to analyze the effect of before and after the applied of make a match in improving the learning outcomes of social science in elementary school. The study used a meta analysis method. This research begins by formulating the topic to be examined, make a statement of the problem, and at the final stage is to search relevant articles to data collections. The data is obtained by searching online journals through google scholar with search keywords “make a match”,”learning outcomes”, and “learning social science in elementary school”. From the research results obtained as many as 35 articles but only 10 articles are relevant for use. The data obtained is processed again using quantitative method. Based on the analysis of student learning outcomes in elementary social studies learning can be increased by an average value before the model is applied to make a match of 45 can increase by 10 to 55. Keywords: Make a Match, Learning Outcomes, Learning Social Science In Elementary School.